A comparative study of the effect of varying wall heat flux on melting characteristics of phase change material RT44HC in rectangular test cells. (October 2019) - Fadl, Mohamed; Eames, Philip C.
Highlights: Experimental investigation performed of melting of RT44HC in a vertically oriented test cell. Uniform wall heat flux values were applied to both the left and right sides of the test cell. The melt fraction development with time was determined using image processing technique. Abstract: Results of an extensive experimental investigation performed to study the effect of different values of wall heat flux in a rectangular PCM (phase change material) test cell on the melting process are presented. A new experimental system consisting of a rectangular cross-section test cell formed from polycarbonate sheet, copper plates and mica heaters was constructed. During experiments uniform wall heat flux (q″wall  = 675, 960 and 1295 W/m 2 ) were applied to both the left and right sides of the test cell. Thermocouples were used to measure the temperature at different locations inside the PCM and on the surface of the copper plates and an infrared camera was used to measure the polycarbonate sheet external surface temperature distribution. The results show the expected strong correlation between the magnitude of wall heat flux and the melt fraction in the PCM as it drives the convective heat transfer. The transparent polycarbonate wall makes it possible to observe the location of the solid/liquid interface and determine melt fractions. The experiments have produced a significant experimental data set for the validation of numerical models simulating the solid/liquid phase change process and PCM melting in geometrical configurations relevant to, for example, latent heat thermal energy storage systems.